Inkjet-printed polymer-fullerene blends for organic electronic applications - Choulis, Stelios A.; Hermerschmidt, Felix; Cambarau, Werther; Waldauf, Christoph; Christodoulou, Constantinos; Pacios, Roberto; Neophytou, Marios (My University, 2012)
Organic field effect transistors, photodiodes and solar cells based on polymer-fullerene blend active layers are printed electronic applications under intense studies. We show that the viscosity of the inkjet formulation, substrate temperature, drop spacing and the height of the droplet in relation to the surface are critical parameters to achieving high quality inkjet-printed polymer-fullerene based active layers. The effect of the above processing parameters on the performance of polymer-fullerene based organic solar cells is presented
Keywords: Fullerenes; Organic field-effect transistors; Polymers; Solar cells; Ink-jet printing; Organic electronics